Structural Health Monitoring of Bridges Using WSNs - et. al., Vinutha B, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Wireless sensor networks (WSNs) for Structural health monitoring (SHM) has earned immense attention in research as it has potential to decrease expenses associated with the maintenance cum installation of these monitoring systems. SHM systems, traditionally are being utilized to screen perilous substructures such as bridges, tall buildings, fields and is capable to increase structure lifetime and safety of public. Earlier wired networks were used by SHM. But this resulted in heavy cost in terms of maintenance and deployment. This project introduces a wireless sensor network using Bluetooth nodes for detection of damage if any in any type of structure in which the data is processed locally in real time and helps in sending alerts once the damage is identified.